Prevalence and associated factors of chronic constipation among Japanese university students - Vu, Nhu Thi Hanh; Quach, Duc Trong; Miyauchi, Shunsuke; Luu, Mai Ngoc; Yoshida, Mahoko; Nguyen, Doan Thi Nha; Yoshino, Atsuo; Miyaka, Yoshie; Okamoto, Yuri; Oka, Shiro; Hiyama, Toru (Frontiers in Public Health, 2024)
Background Chronic constipation (CC) is one of the most frequently reported gastrointestinal disorders in the general population and a prominent problem among university students. The study aimed to evaluate the prevalence and the associated factors of CC among Japanese university students. Methods This cross-sectional study was conducted among university students at Hiroshima University, Japan. Students answered the web questionnaire when making a web reservation for the health checkup (April 1 to May 31, 2023). The web questionnaire consisted of four sections, including baseline characteristics, lifestyle factors, family history of CC, and three scales to assess depression and eating disorders: the Beck Depression Inventory (BDI), Eating Attitudes Test (EAT)-26 and Bulimic Investigatory Test (BITE). CC was diagnosed using Rome IV criteria. The multivariate logistic regression model was used to determine CC-related factors. Results Out of 10,500 individuals who participated in the annual health checkup, 7,496 participants answered the web questionnaire, of whom 5,386 answered all the survey questions. The mean age of the students was 21.1 ± 4.1 years. The male-to-female ratio was 1:1.17. The prevalence of CC was 13.7%. Factors significantly associated with CC in the multivariate model were first-degree family members with CC [Odd ratio (OR): 2.77, 95% confidence interval (CI): 2.31–3.31], severe depression according to BDI scale (OR: 2.59, 95% CI: 1.96–3.43), female sex (OR: 2.00, 95% CI: 1.69–2.36), and short sleep duration of 6 hours or less per day (OR: 1.28, 95% CI: 1.09–1.50). Lack of physical exercise tended to be associated with CC (OR: 1.19, 95% CI: 1.00–1.40). Conclusions CC is prevalent among Japanese university students. Significant risk factors for CC included the first-degree family history of CC, severe depression, female sex, and short sleep duration. Lack of physical exercise tended to be associated with CC. This may contribute to implementing suitable education health programs, health care professionals, and public health policies to identify individuals at risk for CC to prevent and treat CC effectively.